Genome-Wide In Silico Analysis of 1-Aminocyclopropane-1-carboxylate oxidase (ACO) Gene Family in Rice (Oryza sativa L.) - Jing Xia; Yingsheng Qiu; Wanli Li; Yingcheng Zhang; Linxin Liu; Yi Wang; Wangshu Mou; Dawei Xue (Plants)
The plant hormone ethylene elicits crucial regulatory effects on plant growth, development, and stress resistance. As the enzyme that catalyzes the final step of ethylene biosynthesis, 1-Aminocyclopropane-1-carboxylic acid oxidase (ACO) plays a key role in precisely controlling ethylene production. However, the functional characterization of the ACO gene family in rice remains largely unexplored. In this study, we performed a phylogenetic analysis of seven OsACO genes (OsACO1–OsACO7), which were classified into three subfamilies (Types I, II, and III). The members within the same clades exhibited similar tertiary structures and conserved protein motifs. We conducted inter/intraspecies covariance assays of OsACOs to elucidate their evolutionary and duplication events. Numerous cis-acting elements identified in OsACO promoter regions are associated with development, hormonal stimuli, and environmental responses. The expression assay by RT-qPCR revealed that OsACO genes exhibited tissue-specific expression and were significantly altered under various abiotic stresses, indicating their potential involvement in these processes regulated at the transcriptional level. Additionally, we predicted candidate-targeting miRNAs and identified putative cysteine sites of S-nitrosylation (SNO) and S-sulfhydration (SSH) in OsACOs, providing insights into their post-transcriptional and post-translational regulatory mechanisms. These findings pave the way for the further investigation of OsACO functions and their potential applications in improving rice growth and stress resilience by modulating ethylene biosynthesis.